Analisis Jaringan Media Sosial Tentang Eksistensi Kaum Borjuis Dalam Budaya Pop Citayam Fashion Week - Khairul Syafuddin; Hayu Lusianawati (Universitas Bina Sarana Informatika, 2023)
Citayam Fashion Week has become a pop culture that is known by many people. This culture is known as a culture that appears in the midst of marginalized subordinate communities in urban society. Pop culture, which should be a place of expression for young people, eventually disappeared. This happened because there were bourgeois who entered with personal interests. This phenomenon causes the subordinates to be increasingly marginalized. This was increasingly felt when Baim Wong tried to register Haki from that culture. Negative responses then appeared from netizens on Twitter, including Ernest Prakasa and Ridwan Kamil. This ultimately creates a network of interactions that are strong enough to shape public opinion. The purpose of this study was to find out the interaction that was formed about the Citayam Fashion Week phenomenon which focused on the issue of Haki registration carried out by Baim Wong. The interactions that appear on Twitter also form a social-cyber reality triangle. The method in this study uses a qualitative approach. Researchers focused on three Twitter accounts, namely @assumco, @ridwankamil, and @ernestprakasa. The three accounts were chosen because they represent different parties, namely online media, the government, and artists. In addition, this study uses social media network analysis techniques. The choice of this analysis technique is because this research focuses on interactions between users. Besides that, the content on Twitter is used as interaction support data that is analyzed.